Multiple foci of commitment in a professional service firm: balancing complex employment relations. (9th June 2016) - Olsen, Karen M.; Sverdrup, Therese; Nesheim, Torstein; Kalleberg, Arne L.
Abstract : Employees of professional service firms (PSFs) have attachments to multiple groups, which may be either compatible or conflicting: their employer, their clients and their profession. We analyse the antecedents of commitment to these three foci based on a survey of 510 employees in a large PSF in Norway. The main findings are as follows: (1) low quality of internal work relations is negatively associated with employer commitment and draws employees towards external foci of commitment – the clients and the profession; (2) role conflict is associated with stronger commitment to the client organisation and the profession; and (3) autonomy and transferability of skills are associated with stronger commitment to the profession, but does not undermine commitment to the employer. The article contributes to our understanding of the conditions under which employees identify with external groups and when commitment to the employer may be compromised. The findings have implications for how managers can help to increase the commitment of employees involved in complex employment relations.